Distinctions in Practitioner Research between Professional Practice and Research Practice - Simon, Gail (Murmurations: Journal of Transformative Systemic Practice, 2022)
Practitioners undertaking research into their professional practice and those involved in evaluating it often struggle to identify distinctions between the professional practice under investigation and the research practice used to study it. This paper identifies ten areas of distinction between professional practice and research practice. It provides some example questions under each of the ten categories. These questions can be adapted for practitioner researchers as both a preparation exercise and to develop documentation to submit with research proposals or research ethics applications. The paper starts with a definition of practitioner research and then gives a brief history of practitioner research followed by reflections on the relationship between academic and professional knowledge and decolonising practitioner research. The material in this paper was originally delivered at the 7th International Conference on Professional and Practice Based Doctorates, UKCGE, 25th February 2021 (Simon, 2021).